Wash functions downstream of Rho1 GTPase in a subset of Drosophila immune cell developmental migrations. - Verboon, J.M.; Rahe, T.K.; Rodriguez-Mesa, E.; Parkhurst, S.M. (Molecular Biology of the Cell, 2015)
Drosophila immune cells, the hemocytes, undergo four stereotypical developmental migrations to populate the embryo, where they provide immune reconnoitering, as well as a number of non-immune-related functions necessary for proper embryogenesis. Here, we describe a role for Rho1 in one of these developmental migrations in which posteriorly located hemocytes migrate toward the head. This migration requires the interaction of Rho1 with its downstream effector Wash, a Wiskott-Aldrich syndrome family protein. Both Wash knockdown and a Rho1 transgene harboring a mutation that prevents Wash binding exhibit the same developmental migratory defect as Rho1 knockdown. Wash activates the Arp2/3 complex, whose activity is needed for this migration, whereas members of the WASH regulatory complex (SWIP, Strumpellin, and CCDC53) are not. Our results suggest a WASH complex-independent signaling pathway to regulate the cytoskeleton during a subset of hemocyte developmental migrations.